Classroom Video Data and the Time-Image: An-Archiving the Student Body. - de Freitas, Elizabeth (Deleuze Studies, 2015)
Video data has now become the most common form of data for educational researchers studying classroom interaction and school culture. Software protocols for analysing vast archives of video data are deployed regularly, allowing researchers to annotate, code and sort images. These protocols are often applied by researchers without reflection or reference to the extensive philosophical work in film and media studies. Without exception, this research treats the video image as movement-image or picture, a recording of 'raw data', indexical of a given time-space relationship. In this article I situate this kind of research within the history of scientific cinema, drawing on Deleuze's books on cinema, as well as his ideas on colour and figure from The Logic of Sensation, to propose an alternative way of analysing video data. One of the central claims of Deleuze in Cinema 2 is that the time-image reconfigures bodies as expressions of force - the body becomes a 'shock of forces'. I argue that such an approach allows us to study the student body as less a phenomenological organism with built-in 'I can' cognitive and motor capacities, and more an indeterminate crystalline contraction and expansion of intensity. I present an example of how to study classroom video data as time-image, and explore the implications of such work for education research.